2013
DOI: 10.1021/mp300712a
|View full text |Cite
|
Sign up to set email alerts
|

The Brain Entry of HIV-1 Protease Inhibitors Is Facilitated When Used in Combination

Abstract: One hypothesis for persisting HIV-associated neurocognitive disorders (HAND) in effectively treated individuals is the limited permeation of antiretroviral agents (ARV) across the blood-brain barrier (BBB). However, the physicochemical factors limiting the brain entry of a given ARV and the mutual interactions of combined drugs on their brain entry have not been properly characterized. Using transporter kinetic measurements, we show that large lipophilic drugs such as protease inhibitors (PI) have strong bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…However, there is extensive evidence of HIV-mediated disruption of the blood brain barrier resulting in increased entry of normally excluded small molecules and serum proteins (6163). In addition to HIV-mediated effects, even in the absence of virus, CNS accessibility is not necessarily as restricted as anticipated, as brain entry can be facilitated if the drugs are given in combination (64). Importantly, animal studies predict that parenchymal concentrations reach levels equal to, or greater than those found in the CSF, suggesting that concentrations attained in the human brain may be higher than current clinical estimates (65, 66).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is extensive evidence of HIV-mediated disruption of the blood brain barrier resulting in increased entry of normally excluded small molecules and serum proteins (6163). In addition to HIV-mediated effects, even in the absence of virus, CNS accessibility is not necessarily as restricted as anticipated, as brain entry can be facilitated if the drugs are given in combination (64). Importantly, animal studies predict that parenchymal concentrations reach levels equal to, or greater than those found in the CSF, suggesting that concentrations attained in the human brain may be higher than current clinical estimates (65, 66).…”
Section: Resultsmentioning
confidence: 99%
“…Ritonavir is globally used clinically as a boost for other antiretrovirals to increase bioavailability because it is a potent inhibitor of cytochrome P450, which metabolizes these compounds (82). Increased bioavailability of co-administered compounds with high CNS penetrance likely leads to higher brain levels of these compounds (64). Additionally, Ritonavir-boosted regimens are still commonly prescribed in resource-limited settings as first-line treatment, making it globally among the most-prescribed treatment options (83).…”
Section: Resultsmentioning
confidence: 99%
“…PIs may influence drug penetration by inhibiting drug efflux transporters, such as P‐glycoprotein and breast cancer resistance protein, as shown in vitro by Marzolini et al . . Age may be a contributing factor in increasing drug concentration in the CSF, as increased BBB permeability, lower CSF production and reduced transporter function have been suggested to occur in older adults .…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that lipophilic drugs such as protease inhibitors (PI) have a high affinity for drug efflux transporter at BBB, thereby prevent their entry into the brain. However, in combination, the PIs of higher affinity will bind to the transporter and thereby preventing the efflux of the coadministered PIs that facilitate its brain entry [113]. To enhance drug delivery to the brain, various strategies such as non-invasive methods, including drug modification to its lipophilic analogues, pro-drugs, chemical drug delivery, carrier-mediated drug delivery, receptor/vectormediated drug delivery, and intranasal drug delivery are widely used [102,[114][115][116].…”
Section: Novel Approaches and Challengesmentioning
confidence: 99%